Study of double parton interactions in diphoton plus dijet events in p<(p)over bar> collisions at root s = 1.96 TeV - Abazov, V. M. (2016)
We use a sample of diphoton + dijet events to measure the effective cross section of double parton interactions, which characterizes the area containing the interacting partons in proton-antiproton collisions, and find it to be sigma(eff) = 19.3 +/- 1.4(stat) +/- 7.8(syst) mb. The sample was collected by the D0 detector at the Fermilab Tevatron collider in p (p) over bar collisions at root s = 1.96 TeV and corresponds to an integrated luminosity of 8.7 fb(-1).